2021
DOI: 10.1080/10872981.2021.2007577
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of psychological factors related to academic pressure faced by medical students in the central and highland regions of Vietnam

Abstract: Medical students experience extensive pressure during their undergraduate courses. Given the complex associations between psychological factors in association with academic pressure. We investigated the study with objectives: To examine psychological factors related to academic pressure by analysing interactions between ‘study motivation’, ‘study environment’, ‘study conditions’, ‘teacher quality’, ‘training programme’, ‘management system’, ‘evaluation’, and ‘extracurricular activities’ using a network analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…It may even be higher than in high school. A public opinion poll found that approximately 80% of college students around the world said they were under academic stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…It may even be higher than in high school. A public opinion poll found that approximately 80% of college students around the world said they were under academic stress [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Network analysis has been applied to various psychological sciences such as depression, social anxiety disorder, and personality disorder [ 6 ]. In recent publications, the network structure was used to examine psychological factors related to academic pressure in medical students [ 7 ]. Similar to health psychology, the Online Learning Readiness Scale (OLRS) contains complex interactions between individual psychological factors (e.g., motivation, self-control, self-learning), environmental factors (e.g., communication), and individual capacities (e.g., computer skills or internet skills) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%